2016
DOI: 10.21157/ijtvbr.v1i2.5944
|View full text |Cite
|
Sign up to set email alerts
|

2. Characterization Of Lactic Acid Bacteria (LAB) Origin Sumatran Orangutan (Pongo abelii) In Zoo Bukittinggi Based On Analysis 16 S rRNA

Abstract: The purpose of this study was to characterize the bacterial 16S rRNA gene of Sumatran orangutan (Pongo abelii) Bukittinggi West Sumatera zoo. The sample used in this study are lactic acid bacteria of the Sumatran orangutan (Pongo abelii) derived from zoo Bukittinggi West Sumatra Indonesia. This study was an exploratory study that conducted at the Laboratory through several stages. The first stage was the isolation of LAB from faeces of Sumatran orangutans using MRS agar medium and then cultured in a liquid med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Hasil penelitian terhadap orangutan Kalimantan (Pongo pygmaeus) di Taman Safari Indonesia ditemukan 5,9x10 7 koloni bakteri asam laktat [5], sedangkan pada orangutan Sumatera (Pongo abelii) terdapat 7,2x10 6 koloni BAL, dengan ciri-ciri bakteri Gram positif, cocus dan basil [6]. Karakterisasi BAL pada orangutan sumetera yang ada di kebun binatang bukit tinggi dengan Gen 16S rRNA juga telah dilakukan oleh Hajar et al (2016) ; hasil penelitian ini menunjukan bahwa BAL pada orangutan Sumatera memiliki karakter yang dekat dengan BAL strain Lactobacillus helveticus strain IMAU50151 dengan tingkat homologi 89% [7]. Hasil penelitian Septiarini et al (2011) bahwa BAL dari feses orangutan (Pongo pygmaeus) mampu menghambat bakteri enteropatogen (Escherichia coli, Salmonella, dan Shigella) karena memiliki aktivitas antimikroba [8].…”
Section: Pendahuluanunclassified
“…Hasil penelitian terhadap orangutan Kalimantan (Pongo pygmaeus) di Taman Safari Indonesia ditemukan 5,9x10 7 koloni bakteri asam laktat [5], sedangkan pada orangutan Sumatera (Pongo abelii) terdapat 7,2x10 6 koloni BAL, dengan ciri-ciri bakteri Gram positif, cocus dan basil [6]. Karakterisasi BAL pada orangutan sumetera yang ada di kebun binatang bukit tinggi dengan Gen 16S rRNA juga telah dilakukan oleh Hajar et al (2016) ; hasil penelitian ini menunjukan bahwa BAL pada orangutan Sumatera memiliki karakter yang dekat dengan BAL strain Lactobacillus helveticus strain IMAU50151 dengan tingkat homologi 89% [7]. Hasil penelitian Septiarini et al (2011) bahwa BAL dari feses orangutan (Pongo pygmaeus) mampu menghambat bakteri enteropatogen (Escherichia coli, Salmonella, dan Shigella) karena memiliki aktivitas antimikroba [8].…”
Section: Pendahuluanunclassified
“…Studies on Sumatran orangutans, in captivity or nature reserves, found LAB colonies with Gram-positive cocci and basil bacteria. The characterization of LAB from Sumatran orangutans in high hill zoos with the 16S rRNA gene has also been carried out [11]. The results indicated that the LAB in Sumatran orangutans are closely related to the Lactobacillus helveticus IMAU50151 strain, with a homology of 89%.…”
Section: Introductionmentioning
confidence: 99%